Attitude of The Notary Public Towards The Request for The Cancelation of The Prenuptial Agreement Deed as A Result of The Marriage Annulment and The Consequences for Third Parties - Putri Ridzka Maheswari Djasmine; Fully Handayani Ridwan (Faculty of Law, Universitas Pekalongan, 2022)
The existence of an annulment of marriage raises the question on how the attitude of the Notary Public towards the request for the cancelation of the prenuptial agreement deed as a result of the marriage annulment and the consequences for third parties. This study aims to provide an understanding to the reader about how the regulation and consequences of marriage annulment on the prenuptial agreement deed in Indonesia. Based on the study that has been done, it can be concluded that the cancelation of the existing prenuptial agreement deed should be done through an application to the Court, not with a notarial deed of cancelation, so that if the cancelation is problematic or detrimental to a third party in the future, the third party cannot file a civil lawsuit or criminal charge against a Notary Public. The existence of an agreement made with a third party is still valid based on the making of the agreement itself, which is assumed to have fulfilled the requirements stipulated in the Civil Code, laws and regulations, and does not violate the law also the prenuptial agreement deed which remained valid when it became the basis for making the agreement with a third party. Therefore, the agreement remains valid and must be implemented so that third parties with good intentions are not harmed. Regarding who should be responsible later, by all means, is who makes the agreement with the third party.